PENGARUH PERMAINAN EDUKATIF TERHADAP KEBUGARAN JASMANI ANAK TAMAN KANAK-KANAK - Asep Deni Gustiana; Ryan Dwi Puspita (Universitas Pendidikan Indonesia, 2020)
The purpose of this research was to test the effect of educative games on children' physical fitness in Kindergarten. This research was conducted based on the empirical findings that show that the number of children in Kindergarten experienced excessive fatigue after doing activities. Besides the children body mass index, many indicators are included in the category of obesity. The one that causes the phenomenon is the low physical fitness of the children. The problem demands a learning approach or method to handle it without causing excessive fatigue on children. This research was conducted by using the quasi experimental method. The subjects in this study were 30 Kindergarten children in Sukasari Sub-district, Bandung. The results showed p 0.05 which means that there was a significant difference in physical fitness between the control class and the experimental class in post-test with an average score 3.26 for control group, and 6.67 for the experimental group. The results of validation and empirical data showed that learning educational game model gives a significant influence on the physical fitness of Kindergarten children. The learning process was also more enjoyable and engaging. Thus, learning with educative game methods can be considered as an alternative for learning to improve the children physical fitness. This research recommendation is addressed to Kindergarten teachers, Kindergarten school principals, and further researchers.